Impact of a postpartum care rehabilitation program to prevent postpartum depression at a secondary municipal hospital in Qingdao China: a cross-sectional study - Xiaoqian Zhang; Xiaoli Zuo; Catharina Matheï; Bert Aertgeerts; Masoud Afnan; Tang Li; Frank Buntinx; Mieke Vermandere (BMC, 2023)
Abstract Background The emerging postpartum rehabilitation (PPR) program in Chinese hospitals characterized by applying ongoing medical care through traditional cultural practices shows a protective effect in early puerperium in China. This study explores the benefit of PPR program practices to postpartum depression (PPD) and the influencing factors for PPD among Chinese women during the first postnatal six weeks. Methods The cross-sectional study included 403 participants and was conducted in a Secondary Municipal Hospital in Qingdao, China, from 01 to 2018 to 31 December 2021. Information on this PPR program was collected during the six-weeks postpartum consultation, including the Edinburgh postnatal depression scale (EPDS) scores, the measurement results for diastasis recti abdominis, and the international physical activity questionnaire (long form) (IPAQ-L) scores. Logistic regression models were used to examine the effect of the PPR program on PPD among the local population. The secondary aim of this study was to investigate possible influencing factors for PPD, such as coronavirus disease 2019 (COVID-19), physical exercises, etc. Results PPR program has shown a positive effect in preventing PPD (p < 0.001) and diastasis recti prevalence (p < 0.001) during the six-weeks postnatal control in Qingdao, China. Better post-pregnancy weight reduction (p = 0.04) and higher metabolic equivalent of task (MET) value (p < 0.001) were noticed in the non-PPR group. Furthermore, lower PPD risk was associated with factors such as longer relationship duration years (2-5 years) (p = 0.04) and exercising one to three times a week (p = 0.01). A higher PPD risk was related to factors such as urinary incontinence during the postpartum period (p = 0.04) and subjective insomnia (p < 0.001). No significant effect was shown between COVID-19 and the EPDS score in this study (p = 0.50). Conclusion Our results suggested that the PPR program provided protection against PPD and diastasis recti during the first six weeks after delivery. Urinary incontinence and subjective insomnia were the main risk factors for PPD, while longer relationship duration years and exercising one to three times a week gave protective effects to PPD. This study emphasized that a comprehensive ongoing medical care program, such as the PPR program, effectively improves women's mental and physical health in the early postpartum in China.